2017
DOI: 10.1136/bjsports-2016-097313
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of prospective epidemiological research into injury and illness in Olympic combat sport

Abstract: There is currently a lack of consensus in the collection of injury/illness data, limiting the development of prevention programmes for combat sport as a whole. However, sport-specific data that identify body areas with high injury frequency can provide direction to clinicians, enabling them to focus their attention on developing pathologies in these areas. In doing so, clinicians can enhance the practical elements of their role within the integrated combat sport performance team and assist in the regular updat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 37 publications
(41 reference statements)
5
57
0
8
Order By: Relevance
“…The median number of reported illnesses per athlete was 2 (IQR 1-4, min-max 0-11) (Table 4). Vertebral column 40 (22) 27 (25) 5 (19) 6 (35) 5 4611 (20) 11 (18) 2 (33) 17 (22) 24 (…”
Section: Illnesses Incidence Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of reported illnesses per athlete was 2 (IQR 1-4, min-max 0-11) (Table 4). Vertebral column 40 (22) 27 (25) 5 (19) 6 (35) 5 4611 (20) 11 (18) 2 (33) 17 (22) 24 (…”
Section: Illnesses Incidence Ratesmentioning
confidence: 99%
“…The observed injury IR is similar, or even higher, than corresponding rates among able-bodied athletes. 16,[23][24][25] The only comparable study of injuries over time in Paralympic athletes reported an IR of 3.9/1000 hours among wheelchair fencers. 26 In the present study, also a high IP was reported (68%).…”
Section: Sports-related Injuriesmentioning
confidence: 99%
“…Competition fights consist of rounds that typically last two minutes each. To compete on an international level elite athletes train five to seven times a week including full-contact sparring fights for competition simulation [3][4][5][6]. Since injury risk in taekwondo was the highest compared to all other sports during the Olympic games 2012 there is growing interest in injury rates and prevention [3,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…But one must consider that athletes spend a lot more time training than competing [16]. Furthermore, there is also the need to provide data on injury profiles between training and competition in martial arts [4,9,10,17,18]. This study aimed to compare exposure-adjusted injury incidence rates of training and competition in elite taekwondo athletes over a period of 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Las lesiones deportivas afectan la funcionalidad del deportista llevándolo a alterar sus actividades de la vida diaria, las lesiones pueden producirse en cualquier momento del día del deportista y tienen diferentes factores etiológicos como sexo, nivel de competición, tipo de deporte, factores intrínsecos y extrínsecos. Las lesiones pueden darse en diferentes deportes como futbol, judo, balonmano, baloncesto y voleibol reportándose en mayor medida lesiones de cuello de pie como esguinces, rodilla como ruptura de ligamento cruzado anterior y posterior, lesiones de cabeza y cara, muñeca, espalda baja, hombro (12)(13)(14)(15)(16)(17)(18). La fisioterapia es una de las áreas de la salud que trabaja en el deporte de alto rendimiento con el fin de garantizar que el deportista se encuentre en óptimas condiciones para afrontar competencias a nivel nacional e internacional.…”
Section: Introductionunclassified